ANALISIS PENGARUH CITRA MEREK, BUKTI FISIK, KEHANDALAN, DAN JASA PORTOFOLIO TERHADAP KEPUASAN NASABAH TABUNGAN SIMPEDES PADA PT BANK RAKYAT INDONESIA (PERSERO), Tbk KANTOR CABANG KUDUS - Harlyna Kusumawati; Ida Savitri Kusmargiani (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
The study aimed to analyze the influence of brand image, tangible, reliability, and service portofolio on the customer satisfaction of Simpedes saving at PT Bank Rakyat Indonesia (Persero) Tbk. Kudus Branch Office. Data collection method used purposive sampling technique, with samples from 100 respondents. The analysis model used in this research is Linear Regression Analysis Model while the data analysis techniques using the F test, t test and the coefficient of determination (R2). In addition, it also tests the quality of the data in the form of test validity and reliability, as well as a classical assumption test normality test, multicollinearity, heteroscedasticity test and autocorrelation test. Test data indicate that the data is valid and reliable and free from irregularities classical assumptions. The analysis and discussion showed that brand image, tangible, reliability, and service portofolio simulataniously significant influence on the customer satisfaction of Simpedes saving in PT Bank Rakyat Indonesia (Persero), Tbk Branch Office Kudus. Variable brand image, tangible, reliability, and service portofolio partially significant influence customer satisfaction of Simpedes saving in PT Bank Rakyat Indonesia (Persero), Tbk Branch Office Kudus.